EFFECT OF USER CONVENIENCE, TRUST AND SECURITY INSTAGRAM SOCIAL MEDIA ON CONSUMER BUYING INTERESTFOR STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS UNIVERSITAS MALIKUSSALEH - Vena Mauliza; T. Edyansyah; Heriyana; Rusydi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study examined the effect of convenience, trust, and security on Instagram users' interest in using the platform for online shopping. The sample consists of students from the Faculty of Economics and Business at Malikussaleh University, selected using a purposive sampling method with 120 respondents, following the Hair et al. formula. Primary and secondary data were collected from the Faculty of Economics and Business at Malikussaleh University. Data analysis employed multiple linear regression . The study revealed that convenience did not significantly influence consumer purchase interest. This finding suggests that while convenience is substantial. Without assurances of security, consumers may hesitate to shop on Instagram. Trust, however, shows a positive and significant impact on consumer purchasing interest. Consumers perceive Instagram as a secure platform that guarantees product quality and seller reputation. Similarly, security positively influences consumer purchasing interest, as Instagram provides security measures to protect personal data and ensures product reliability.